Development of Audio-Visual Physics Animation Media to Improve Students’ Understanding of Concepts and Creativity - Fita Permata Sari; Salamun Hadi Subroto; Faruq Haroky (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
Increasing technology in this modern era of globalization can be applied to the world of education as a facility to facilitate the learning process delivered. Applying technology can help to learn that are hampered by distance can be overcome by distance learning. Distance learning has not yet become a part of most schools in Indonesia, especially elementary schools. So, there is a need for further research to produce audio-visual animation media so that it can help to learn for elementary school students. This type of research is an educational R&D development research (Educational Research and Development) referring to the ADDIE development model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The type of data used is descriptive qualitative and quantitative data. Techniques for data collection are using questionnaires and questions. This shows no difference between using audio-visual animation learning media for science-themed to permanently save energy and other media provided by educators in schools to improve students’ conceptual understanding and creativity.